Analisis Prosedur Pelaksanaan Eksekusi Hukuman Cambuk (Uqubat) dalam Perkara Jinayah di Mahkamah Syar’iyah - Hasbi Shiddiq El-Islamy; Kayla Audia Zahrani; Muhamad Mulki; Deden Najmudin4 (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of caning punishment (uqubat) in jinayat cases in Aceh constitutes a form of regional autonomy recognized within Indonesia’s national legal system. Normatively, the execution of caning punishment has been comprehensively regulated under Aceh’s Jinayat Law and Jinayat Procedural Law. However, judicial practice reveals a gap between normative regulation (das sollen) and its implementation (das sein), particularly regarding juridical synchronization, procedural compliance, and sentencing effectiveness. This study aims to examine the procedures for executing caning punishment in jinayat cases before the Syar’iyah Courts, assess the conformity between legal norms and implementation practices, and analyze the implications of procedural compliance for the effectiveness of jinayat sentencing. This research employs a normative juridical method using statutory and conceptual approaches. The data consist of primary and secondary legal materials analyzed through qualitative prescriptive analysis. The study applies the concepts of legal certainty, due process of law, as well as principles of Fiqh jinayah and human rights as its analytical framework. The findings indicate that although the execution procedures of caning punishment normatively comply with legality and due process principles, practical challenges such as institutional coordination and procedural inconsistency continue to affect sentencing effectiveness. The novelty of this research lies in its integrative analysis that positions procedural compliance as a convergence point between jinayat procedural law, Fiqh jinayah, and human rights protection. This study contributes to the academic discourse by strengthening the conceptual understanding of caning punishment execution and offering insights for enhancing the legitimacy and effectiveness of jinayat law enforcement in Aceh.